Strategi Kesantunan Berbahasa Mahasiswa UPS Tegal dalam Percakapan WhatsApp - Leli Triana; Tri Mulyono (Universitas Pancasakti Tegal, 2019)
This research aims to describe the politeness strategies of UPS Tegal students' language proficiency in communicating with lecturers through WhatsApp media. This type of research is qualitative descriptive. Data used in research this is what UPS Tegal students said to the lecturer when communicating through WhatsApp media. The method of providing data in this study was the method of listening with tapping techniques as a basic technique, followed by a skillful and involved listening and note taking technique. Data analysis method used is the pragmatic matching method. Presentation of data analysis is the informal method. The results showed that there were four politeness strategies used, which were straightforward strategies, indirect strategies, positive politeness strategies, and negative politeness strategies. (1) A straightforward strategy in the form of very short, firm, and straightforward speeches with concise, concise, direct targets. Speech with this strategy is a polite speech. (2) Indirect strategies of declarative speech intended to govern (imperative). (3) Positive politeness strategies in the form of sympathy, involving speakers and interlocutors in one activity, giving reasons, and giving gifts. (4) Negative politeness strategies in the form of speech containing pessimism, humbling, apologizing, and asking questions